Efektivitas Man-Portable Anti-Tank System Dalam Perang Modern: Studi Kasus Javelin Dan NLAW Dalam Konflik Rusia-Ukraina - Zidan Patrio; Agussalim Burhanuddin (Pusat Riset dan Inovasi Nasional, 2023)
The war between Russia and Ukraine has recently been in the international spotlight. One of the things seen is the weapons technology used. The modernization of weapons technology has prolonged the war on both sides. This article will discuss Javelin and NLAW which are types of portable anti-tank missiles and their use in the Russia-Ukraine war. Man-Portable Anti-tank Systems are shoulder-fired missiles that are used to destroy opposing tanks. Weapons such as the Javelin and NLAW are the result of the development of earlier versions of the Anti-Tank Guided Missile. These